Identification of Source Mechanisms for the August 5 2018 Mw 6.9 and the August 9 2018 Mw7.0 Lombok Earthquakes - Priadi, Ramadhan; Perdana, Yusuf Hadi; Wijaya, Angga; Suardi, Iman (Universitas Negeri Surabaya, 2020)
A series of earthquakes with magnitudes ranging from 5.8 to 7.0 occurred in Lombok in the period of July to August 2018. Two events occurred consecutively, the 6.9 on August 5, 2018 (11:46:38 UTC), and the 7.0 on August 9, 2018 (14:56:28 UTC). Those phenomena are rare because earthquakes usually require a relatively long time to accumulate their energies before being released. Because of those events, so an explanation is needed to explain what happened at the source. In this context, this study aims to determine the relations between the events based on the asperity zone and the slip distributions. Modeling was performed using teleseismic data and seismic inversion of body waves at low frequencies. The result shows that the asperity zone of 6.9 is at 0 km in a strike-direction and -18 km wide in a dip-direction with a maximum slip of 1.3 m, whereas, for the 7.0 event, the asperity zone is at -36 km in the direction of the strike and -7 km in the direction of the dip. Both events have the asperity in the up-dip section with an upward slip distribution towards the up-dip. The slip distribution of the first event and the second one has a relationship because the 6.9 earthquake slip leads to the 7.0 earthquake fault plane. The relation is suspected to be due to the weakening of rock conditions and an enlargement that is limited by space and time during the earthquake. As a result, those two earthquakes are closely related to stress distribution, forming a new asperity zone.